To Bail or Not to Bail: Protecting the Presumption of Innocence in Nevada - McLeod, Brendan (2019)
This white paper aims to discuss the issues associated with bail reform in Nevada, provide an analysis of bail reform efforts across the country, and purpose possible solutions for obstacles to bail reform in Nevada. The white paper’s proposed recommendations for practical bail reform is a three-phase plan to eliminate the injustices that arise from Nevada’s current cash bail model